2022
DOI: 10.21831/cp.v41i2.47956
|View full text |Cite
|
Sign up to set email alerts
|

Improving creativy and learning motivation in basketball through tactical approach

Abstract: Students assumed that learning basketball is less fun and students did not seem interested in following it. The purpose of this study was to determine the effect of a tactical approach in basketball learning on creativity and motivation. The method used in this study was "pre-experimental design" method in the form of "intact-group comparison". The sample in this study was the eleventh graders of State Junior High School 4 Lubuklinggau with total sample of 60 students. The instruments used in this study were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Moreover, TGM demonstrated a superior effect on enhancing students' motivation compared to DIM (F = 65.186; p < 0.001; η 2 p = 0.66). This study's findings corroborate those of Hartati et al [79], who reported a significant difference in motivation between students taught using the TGM and those in the control group. TGM notably enhanced students' motivation to learn basketball.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, TGM demonstrated a superior effect on enhancing students' motivation compared to DIM (F = 65.186; p < 0.001; η 2 p = 0.66). This study's findings corroborate those of Hartati et al [79], who reported a significant difference in motivation between students taught using the TGM and those in the control group. TGM notably enhanced students' motivation to learn basketball.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous researchers have suggested that effective utilization of the TGM in physical education courses can help teachers enhance student motivation for learning [73,74,78]. Hartati et al [79] conducted a study involving 60 middle school students using the tactical games model (TGM) and established a control group to evaluate the effects. The findings indicated that TGM effectively increased the motivation of these students in a basketball learning context.…”
Section: Introductionmentioning
confidence: 99%
“…En la mayoría de estos artículos se usaron las tareas presentadas en este trabajo. (Hartati et al, 2022) Nota: TGA = Tactical Games Approach; SSGs = Small-Sided Games.…”
Section: Evidencias Científicas Del Tga En La Enseñanza De Deportes D...unclassified